Dual-band digital beamforming synthetic aperture radar for earth observation - Gao, S.; Mao, C.; Qin, F.; Patyuchenko, A.; Tienda, Carolina; Younis, M.; Krieger, Gerhard; Glisic, S.; Debski, W.; Boccia, L.; Amendola, G.; Arnieri, E.; et al. (Asia-Pacific Microwave Conference (APMC), 2015)
This paper presents some results of dual-band digital beamforming (DBF) space-borne Synthetic Aperture Radars (SAR). To reduce the cost, size, mass and power consumption of current space-borne SAR systems, a multi-static passive radar concept using DBF, highly integrated analogue and digital circuits and shared-aperture dual-band dual-polarization printed array on printed-circuit-board (PCB) is presented. Such a multi-static SAR system will be employed onboard a constellation of multiple small, low-cost satellites. First, the radar concept is introduced and followed by some results of dual-band shared-aperture antenna arrays. In addition, some results of MMIC and DBF are presented. To verify the simulation results, one prototype C/X dual-band sub-array had been fabricated and measured. The fabrication of X/Ka dual-band SAR system is currently on the way and more experimental results will be presented during the conference.
DLR Import::2019-04-03